2017
DOI: 10.18632/oncotarget.18997
|View full text |Cite
|
Sign up to set email alerts
|

Classical swine fever virus Shimen infection increases p53 signaling to promote cell cycle arrest in porcine alveolar macrophages

Abstract: Classical swine fever virus (CSFV) replicates in macrophages and causes persistent infection. Despite its role in disastrous economic losses in swine industries, the molecular mechanisms underlying its pathogenesis are poorly understood. The virus evades the neutralizing immune response, subverting the immune system to ensure its own survival and persistence. Our genome-wide analysis of porcine alveolar macrophage transcriptional responses to CSFV Shimen infection using the Solexa/Illumina digital gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…However, little is known about its role in the pathogenesis of CSF. In previous study, significantly up-regulated and down-regulated genes were obtained from CSFV Shimen infected group which were compared to the C strain and MOCK infected group (Ning et al, 2017). In this work, we paid attention to AIF1 from the obtained differentially expressed genes to focus on its biological significance in macrophages to CSFV infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, little is known about its role in the pathogenesis of CSF. In previous study, significantly up-regulated and down-regulated genes were obtained from CSFV Shimen infected group which were compared to the C strain and MOCK infected group (Ning et al, 2017). In this work, we paid attention to AIF1 from the obtained differentially expressed genes to focus on its biological significance in macrophages to CSFV infection.…”
Section: Discussionmentioning
confidence: 99%
“…DGE analysis was performed to screen for differentially expressed genes in CSFV-infected PAMs based on previously reported high-throughput sequencing data (Ning et al, 2017), which identified AIF1 as a key gene, and further testing was conducted to confirm its role during infection by CSFV Shimen. The CSFV Shimen strain was obtained from the Control Institute of Veterinary Bioproducts and Pharmaceuticals.…”
Section: Study Design Virus Strain and Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porcine alveolar macrophages (PAMs) were cultured in RPMI 1640 medium (GE, USA) containing 10% fetal bovine serum (FBS; Gibco Life Technologies, USA) at 37 C with 5% CO 2 . The CSFV Shimen strain is from the Control Institute of Veterinary Bioproducts and Pharmaceuticals (Beijing, China) [17]. The PAM cell line 3D4/21 (CRL-2843) was obtained from the American Type Culture Collection (Manassas, VA, USA) [18].…”
Section: Cell Culture and Virusmentioning
confidence: 99%